Employee Performance in High Stressed Indian Garment Industry; a Study on Design & Production House - Style Variations in New Delhi (india) (Vallis Aurea, 2021)
Being universal phenomenon, stress is experienced in everyday human life especially among individuals who work in different industrial set-ups at various levels of jobs. With changing work expectations, competition & environment, increasing workloads and work place politics, stress has become an integral part of employees’ life and affects individual performance. Also, due to an employee’s psychological and physiological reactions to work situation factors directly or indirectly influence the stress to appears, as resultant. Though certain level of work stress instigates the efficiency of work in positive but more stress causes negative impact on individual employee and in turn to organization too. Employees handle such stress without letting it influence their performances but fail to do so with growing work stress beyond certain level. On organization side, it also depends upon type of industry and nature of competition faced by the organization in market. On individual side, this stress impact on performance varies with work experience, demographics and length of service years. In order or assess workplace stress and its influence on individual employee, this study is done on a garment manufacturing organization in India, which is prone to high work stress due to its competitive nature of business.